Promoter hypermethylation and comprehensive regulation of ncRNA lead to the down-regulation of ZNF880, providing a new insight for the therapeutics and research of colorectal cancer - Xiangqian Dong; Yinghui Zhang; Yang Sun; Qiong Nan; Maojuan Li; Lanqing Ma; Lei Zhang; Juan Luo; Yating Qi; Yinglei Miao (BMC Medical Genomics, 2023)
Abstract The human genome encodes more than 350 kinds of Krüppel-associated box (KRAB) domain-containing zinc-finger proteins (KZFPs), KRAB-type ZNF transcription factor family (KZNF) plays a vital role in gene regulatory networks. The KZNF family members include a large number of highly homologous genes, gene subtypes and pseudogenes, and their expression has a high degree of tissue specificity and precision. Due to the high complexity of its regulatory network, the KZNF gene family has not been researched in sufficient, and the role of its members in the occurrence of cancer is mostly unexplored. In this study, ZNF880 was significantly associated with overall survival (OS) and disease-free survival (DFS) in colorectal carcinoma (CRC) patients. Low ZNF880 expression resulted in shorter OS and DFS. Combined with Colon adenocarcinoma (COAD) and Rectum adenocarcinoma (READ) data collection in the TCGA database, we found that ZNF880 was significantly down-regulated in CRC. Further analysis of the sequence variation of ZNF880 in CRC showed that ZNF880 accumulated a large number of SNV in the C2H2 domain and KRAB domain, while promoter region of ZNF880 also showed high methylation in COAD and READ. Combined with the Cbioportal and TIMER databases, the expression of mutant ZNF880 was significantly lower in COAD compared to the wild type. Simultaneously, the lncRNA-miRNA-ZNF880 ceRNA regulatory network was constructed through co-expression and miRNAs target gene prediction, demonstrating the precision of the ZNF880 regulatory network. In addition, the decreased expression of ZNF880 caused the significant immune infiltration decreases of CD8 + cells in COAD. In contrast, the immune infiltration of CD4 + cells and macrophages in COAD is positively correlated with ZNF880. Finally, through protein–protein interaction (PPI) network analysis and transcription factor target gene prediction, we screened out the genes most likely to be related to the function of ZNF880. CENPK, IFNGR2, REC8 and ZBTB17 were identified as the most closely functioning genes with ZNF880, which may indicate that ZNF880 has important links with the formation of cell centromere, tumor immunity, cell cycle and other pathways closely related to the occurrence of CRC. These studies show that the down-regulation of ZNF880 gene is closely related to CRC, and the targeted change of the expression of its regulatory molecules (miRNA and lncRNA) may be a new perspective for CRC treatment.